Long-term IL-2 therapy after transplantation of T cell depleted stem cells from alternative donors in children - Schlegel, Patrick; Teltschik, Heiko-Manuel; Pfeiffer, Matthias; Handgretinger, Rupert; Schumm, Michael; Koscielniak, Ewa; Feuchtinger, Tobias; Klingebiel, Thomas; Bader, Peter; Schlegel, Paul-Gerhardt; Greil, Johann; Lang, Peter (Best practice & research, 2011)
The aim of this pilot study was to evaluate the feasibility of long-term subcutaneous application of low-dose IL-2 in children with malignancies at very high risk of relapse who underwent highly T cell and B cell depleted HLA-identical (MUD) or full haplotype mismatched related hematopoetic stem cell transplantation. We studied 11 patients with acute leukemias/myelodysplastic syndrome and juvenile myelomonocytic leukemia (active disease and/or second stem cell transplantation, n = 8; ≥CR 2, n = 2) and relapsed or progressive Ewings sarcoma (n = 2) who received prophylactic IL-2 treatment for a high probability of disease recurrence after allo-HSCT. Toxicities from IL-2 were transient fever, fatigue and local inflammation. In one patient GvHD grade III with no clear association to IL-2 administration occurred. IL-2 administration was started at median day 57 (range 13-154) post-transplant for a mean duration of 28 days (range 15-250). IL-2 administration clearly increased NK cell activity. 3 of 11 patients (ALL, AML, multifocal Ewings sarcoma) survived with a follow-up of ten years. In conclusion, long-term low-dose IL-2 subcutaneous application is feasible in children due to a low side effect profile even after HLA mismatched transplantation and may be a strategy to prevent relapse in pediatric malignancies with extremely high risk of relapse.
Gesehen am 12.10.2022